ANALYSIS OF THE THRUST ON PROPELLER SHAFT ANGLE ON FISHING VESSEL USING CFD - Prasdika, Tegar Oki; Bahatmaka, Aldias; Andriano, Kriswanto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Indonesian fishing vessels need a prime mover capable of propelling the vessel forward and backward. According to data from the Ministry of Maritime Affairs and Fisheries, many vessels in Indonesia are spread across various State Fisheries Management Areas of the Republic of Indonesia waters. Most of the ships are in the State Fisheries Management Area of the Republic of Indonesia, 712 area, from a total of 4,989 vessels found in the area. This study aims to determine the thrust and torque values generated from the propeller using Ansys CFD (Computational Fluid Dynamics) software to determine the thrust force on the ship. The method used is the operation of the Ansys Fluent program on a computing device to calculate and simulate the effect of thrust on the propeller against the tilt angle of the shafts at 0°, 5°, 10°, 20°, 30°, 40°, 50°, and 60°. Before simulating, a validation process has been performed with an error below 5% in straight conditions without tilt. The results show propellers with various shaft angles have different thrust and torque values. In the simulation of a 50° tilt angle, the thrust value is 55809 N and the torque is 7211.15 Nm, while at a 60° tilt angle, the thrust value is 54582.4 N and the torque is 6193.81 Nm. Therefore, the propeller tilt position of 50° has the appropriate thrust and torque and can produce the optimal thrust force compared to other angles.